Frayer Model Vs. Vocabulary Struggles: A Classroom Breakthrough AT SMPN 1 Tompobulu - Azizah, Wafiq Nur; Natsir, Ratu Yulianti; Hijrah (FKIP Unismuh Makassar, 2025)
This research explores the effectiveness of the Frayer Model as an innovative strategy to enhance vocabulary acquisition among eighth-grade students at SMPN 1 Tompobulu. Responding to the urgent need for more engaging and concept-driven vocabulary instruction, the study employed a quasi-experimental design with two groups: an experimental group and a control group (n = 25 each). Both groups completed pre- and post-tests using multiple-choice questions. Statistical analysis using SPSS 22 revealed a significant improvement in the experimental group’s mean score (from 36.80 to 76.80), compared to the control group (from 50.88 to 55.52). The t-test results (t = 5.951, p < 0.05) confirmed the effectiveness of the Frayer Model over conventional methods. These findings highlight the model’s potential to stimulate deeper student engagement and vocabulary retention, offering valuable pedagogical contributions for English language teaching in secondary education.